Proceedings of the 2016 ACM Conference on Designing Interactive Systems 2016
DOI: 10.1145/2901790.2901824
|View full text |Cite
|
Sign up to set email alerts
|

Developing Compelling Repetitive-Motion Exergames by Balancing Player Agency with the Constraints of Exercise

Abstract: Participation rates in repetitive-motion exercise programs, such as programs for muscle-strengthening and physical rehabilitation, are low. Exergames show promise in encouraging people to exercise, but it is challenging to build compelling games around repetitive exercises. Games involve players making meaningful choices, but repetitivemotion workout programs are rigidly structured, making it difficult to find opportunities for such choices. As such, there is a struggle between providing players with meaningfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We are not the first work to incorporate gamification with strength training. Richards et al [21][22][23] proposed three game design methods to overcome the problem of lacking agency in repetitive-motion exergames. Agency refers to the "ability to act within an environment" [21], and the more agency a game achieves, the better the experience.…”
Section: Strength Training and Playmentioning
confidence: 99%
“…We are not the first work to incorporate gamification with strength training. Richards et al [21][22][23] proposed three game design methods to overcome the problem of lacking agency in repetitive-motion exergames. Agency refers to the "ability to act within an environment" [21], and the more agency a game achieves, the better the experience.…”
Section: Strength Training and Playmentioning
confidence: 99%
“…The first game is Balance of Power, which is a tugof-war style game implemented with the Kinect, while Bundle is a playground-inspired chasing game implemented with smartphones. Brains & Brawn is strategy card game for muscle-strengthening inspired of games like Heartstone and Pokémon [26]. Playtesting the game demonstrated that players were incented to exercise with correct form and showed favorable attitude toward the game.…”
Section: Related Workmentioning
confidence: 99%
“…Further there are exergames that explores the borders of the physical and virtual world [14][15][16][17][18][19][20][21][22]. Exergames focusing on muscle strengthening in general, which are not used for physical treatment are underrepresented in the literature on exergames, although there are some examples [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Behavior Change Theories-Other researchers have focused on the application of health and behavior change concepts within games and gamified applications. Behavior change theories have influenced both the design and evaluation of serious games, particularly those focusing on health promotion and illness management (e.g., tobacco prevention [22], exercise [28], nutrition [19], physical therapy [39], and medication adherence [44]). Recent arguments against the application of purely cognitive models of behavior change (e.g., Transtheoretical Model [38], Health Belief Model [27]) point out their overemphasis on the individual [45] in modeling behavior.…”
Section: Game and Health Frameworkmentioning
confidence: 99%